2021
DOI: 10.1002/solr.202100574
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Ratio of Sn4+ and Sn2+ in Cu2ZnSn(S,Se)4 Precursor Solution via Air Environment for Highly Efficient Solar Cells

Abstract: The use of different Sn valence states (such as Sn4+ and Sn2+) in the Cu2ZnSn(S,Se)4 (CZTSSe) precursor solution is especially important for the quality of the subsequent growth of the CZTSSe films. The latest study has found that replacing SnCl2·2H2O with anhydrous SnCl4 can remarkably improve the performance of CZTSSe solar cells, but it needs to be operated in the glovebox. Herein, for the precursor solution, SnCl4·5H2O powder is used instead of anhydrous SnCl4 in air environment, and the proportion of Sn4+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…[10] Despite this, the efficiency of solutionprocessed Cu 2 ZnSn(S, Se) 4 solar cells still remains much lower than the detailed balance limiting efficiency of 32%, which is hindered by the severe nonradiative recombination and large Voc def resulting from the imperfect crystal quality. [11][12][13][14][15] As the most important process affecting the crystallinity of thin CZTSSe films, selenization needs to be further studied. In general, solid Se particles are widely used as Se source for the postselenization of CZTSSe because of the low toxicity and relatively higher safety.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Despite this, the efficiency of solutionprocessed Cu 2 ZnSn(S, Se) 4 solar cells still remains much lower than the detailed balance limiting efficiency of 32%, which is hindered by the severe nonradiative recombination and large Voc def resulting from the imperfect crystal quality. [11][12][13][14][15] As the most important process affecting the crystallinity of thin CZTSSe films, selenization needs to be further studied. In general, solid Se particles are widely used as Se source for the postselenization of CZTSSe because of the low toxicity and relatively higher safety.…”
Section: Introductionmentioning
confidence: 99%
“…For the kesterite structured CZTSSe system, the main reasons accounting for the severe V OC decit (V OC,def ) include the band tail states generated by the high concentration of deep-level defects and defect clusters 4,6 (e.g., Cu Zn , Cu Sn , and [2Cu Zn + Sn Zn ]), the formation of secondary phases 7,8 (e.g., CuS, SnS 2 and ZnS) during the crystal growth process, and the mismatching energy band alignments between various functional layers. [9][10][11] Several approaches have been attempted to mitigate these issues, including cationic substitution, 12,13 grain growth optimization, [14][15][16] heterojunction post-annealing, 17 graded bandgap engineering, 18 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…, CuS, SnS 2 and ZnS) during the crystal growth process, and the mismatching energy band alignments between various functional layers. 9–11 Several approaches have been attempted to mitigate these issues, including cationic substitution, 12,13 grain growth optimization, 14–16 heterojunction post-annealing, 17 graded bandgap engineering, 18 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…8f), which reduces the concentration of deep defects, fortunately, achieving efficiency of over 11%. 34 In addition, Zhao et al reported a simple and environmentally friendly additive strategy by adding water additives, which can improve the homogeneity and thermogravimetric characteristics of the precursor solution by adjusting the particle size and coordination behavior of the precursor solution, achieving a certified CZTSSe device with a PCE of 12.07%. 140 In 2022, an efficiency of 12.87% was achieved using a two-step cooling strategy, which can suppress the Cu Zn and Sn Zn defects and defect clusters synergistically.…”
Section: Ethylene Glycol Methyl Ether-based Precursor Solution Method...mentioning
confidence: 99%
“…Currently, various environmentally friendly, safe, stable and high-efficiency solvent systems have been successfully developed, including dimethyl sulfoxide (DMSO), N , N -dimethylformamide (DMF), ethylene glycol methyl ether (EGME), thioglycolic acid and ammonia (TGA), and ethylenediamine/ethanedithiol system (EN/EDT). 31–35 Both vacuum method and solution processes have resulted in significant improvements in CZTSSe device performance, 36–39 and the development of PCE evolution is shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%